Impact of Antioxidants on Bond Strength between Resin Composites and Bleached Enamel: An In Vitro Comparative Evaluation - Divyanshu Choudhary; Sandhya K Punia; Yogender Kumar; Shilpi Kushwaha; Shreya Agarwal (Dental Journal of Advance Studies)
Aims and background: The purpose of the study was to assess and compare the impact of different antioxidants, namely Camellia sinensis (Green tea), Aloe Barbadensis Miller (Aloe vera), Ascorbic acid, and Phyllanthus emblica (Amla), on the bond strength of resin composites to bleached enamel in vitro. Methods: A total of 60 intact permanent incisors were collected and mounted in self-cure acrylic resin. The facial surface was flattened using sandpaper. Teeth were divided into two groups on the basis of the bleaching agent used. Group A: no bleaching, Group B: 35% hydrogen peroxide. After bleaching following the manufacturer's instructions the teeth were washed and dried. Group B was further subdivided based on the antioxidants used. B0/C0– No antioxidant, B1/C1 – 10% Green tea, B2/C2 – 10% Aloe vera, B3/C3 – 10% Sodium Ascorbate, B4/C4 – 10% Amla. The flattened and treated enamel surface was bonded to composite resin using plastic molds. Samples were subjected to shear bond strength (SBS) evaluation. The results were analyzed using one-way ANOVA and Post Hoc Tukey's Test to evaluate the differences in the SBS. Results: The highest SBS was presented by unbleached group A (51.520) followed by group B (34.288). 10% sodium ascorbate showed the most potent antioxidant action in reducing bleach effect while 10% Amla gave the worst results. Conclusion: Ascorbic acid enhanced the SBS to enamel bleached with hydrogen peroxide, outperforming Green tea, Aloe vera, and Amla. Clinical significance: Bleaching sometimes fails to completely resolve discoloration, necessitating composite restorations. In these cases, antioxidants can restore the weakened bond strength between bleached enamel and resin composite, which is essential for clinical practice.